2007
DOI: 10.1002/adma.200601759
|View full text |Cite
|
Sign up to set email alerts
|

A Micellar Approach to Magnetic Ultrahigh‐Density Data‐Storage Media: Extending the Limits of Current Colloidal Methods

Abstract: At the ultimate limit of magnetic recording, suitable storage media will consist of nanometer-sized entities, each of which will carry one bit of information. Materials with a high magnetocrystalline anisotropy energy are required to guarantee thermal stability of the ferromagnetic state at realistic operating temperatures. The face-centered tetragonal (fct) L1 0 FePt alloy belongs to the promising class of materials that offer the perspective of storing one magnetic bit per nanoparticle. [1][2][3] Widespread … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
108
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(115 citation statements)
references
References 31 publications
5
108
1
1
Order By: Relevance
“…A H 2 plasma treatment has been successfully used by Wang et al 73 to reduce 25 nm-thick oxidized Fe-layers. Ethirajan et al 74 and Boyen et al 75 have also demonstrated that oxidized (O 2 -plasma treated) FePt and Co NPs, synthesized by the same inverse micelle encapsulation method used in the present work, can be completely reduced by atomic hydrogen exposure. In our samples, the first H 2 -plasma treatment at 300°C resulted in a reduction of the Fe 3+ signal, with 28% metallic Fe detected.…”
Section: A Morphological Characterization (Afm Stm)mentioning
confidence: 85%
“…A H 2 plasma treatment has been successfully used by Wang et al 73 to reduce 25 nm-thick oxidized Fe-layers. Ethirajan et al 74 and Boyen et al 75 have also demonstrated that oxidized (O 2 -plasma treated) FePt and Co NPs, synthesized by the same inverse micelle encapsulation method used in the present work, can be completely reduced by atomic hydrogen exposure. In our samples, the first H 2 -plasma treatment at 300°C resulted in a reduction of the Fe 3+ signal, with 28% metallic Fe detected.…”
Section: A Morphological Characterization (Afm Stm)mentioning
confidence: 85%
“…Magnetic nanoparticle systems are an important research topic for various future applications including magnetic data storage [1], hyperthermia treatment agent [2], etc. Also, finite-size effect study and surface effect study can be performed with magnetic nanoparticle systems as model systems.…”
Section: Introductionmentioning
confidence: 99%
“…In accordance with their natural environment of fabrication (in solution) such nanoparticles are frequently and successfully used in biotechnology [24][25][26][27]. For the application in magnetic storage and spin devices a severe problem is to bring the particles on a supporting sample with the particles well aligned with regards to their crystal structure or magnetic axis [28][29][30]. The latter obstacle is circumvented by alternative methods that directly create the nanostructures on the supporting surface.…”
Section: Introductionmentioning
confidence: 99%
“…To tune the diameter as well as the spacing of the particles the organic spheres are shrunk in a plasma etching step before structure transfer [60][61][62]. A similar technique uses diblock copolymer micelles as selfassembling units which are filled with magnetic or nonmagnetic material [28][29][30][63][64][65]. Magnetic dot arrays can be directly created when magnetic core material is used and the organic shell is removed in oxygen plasma [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation